การเปลี่ยนไซโลสเป็นเอทิลีนไกลคอลบนตัวเร่งปฏิกิริยาฐานนิกเกิล - ปัญญา วัฒนะปภาวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The aims of this research were to study the conversion of xylose to ethylene glycol over Ni-based catalyst which have variable on this studied are temperature (423 - 573 K), reaction time (2 - 8 hour), pressure (2 - 5 MPa), xylose/catalyst ratio (1:1 - 1:2), catalysts types, and xylose (1, 5, 10 g). The catalyst was prepared by impregnation technique based on nickel nitrate and lanthanum nitrate over an activated carbon. Also, the catalyst was analyzed by SEM, EDX, XRD, BET, and TPD technique. The conversion of xylose to ethylene glycol was performed in a stainless steel autoclave with a volume of 250 mL with a stirring 600 round/min. All liquid products were analyzed quantity of ethylene glycol by a high-performance liquid chromatography (HPLC). From the results show that if the temperature less than 473 K, xylose will not change 100% and if the temperature more than 473 K, the product will not be ethylene glycol at the pressure less than 3 MPa, the product will be change to high ethylene glycol. if the using time less than or more than 6 hours, the ethylene glycol will be occur below than 6 hours as well. Thus, the optimum condition for conversion of xylose to ethylene glycol were at temperature of 473 K, reaction time of 6 hours, pressure of 3 MPa, xylose/catalyst ratio of 1:1, 0.5LaNi/AC catalyst and xylose 1 gram by the optimum yield of ethylene glycol product was 0.067 gram/ 1 gram of xylose.